2021
DOI: 10.1155/2021/5539584
|View full text |Cite
|
Sign up to set email alerts
|

Shen Shuai II Recipe Attenuates Renal Interstitial Fibrosis by Improving Hypoxia via the IL-1β/c-Myc Pathway

Abstract: Background. Renal interstitial fibrosis is a pathological manifestation of progression of chronic kidney disease induced by various factors. Shen Shuai II Recipe (SSR) has been used in clinical practice for more than 20 years, and clinical studies have confirmed that SSR significantly improves the renal function of patients with chronic kidney disease. However, the specific mechanisms underlying its efficacy require further research. This study aims to explore the influencing factors of renal interstitial fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The major chemical components of SSR, identified by Ultra-High Performance Liquid Chromatography-High Resolution Mass Spectrometry, was reported in our previous study [ 7 ], including rosmarinic acid (21.280 mg/each gram of SSR), amygdalin (6.588 mg/g), salvianolic acid B (1.852 mg/g), caffeic acid (1.390 mg/g), icariin (1.055 mg/g), berberine hydrochloride (0.503 mg/g), codonopsis lactone (0.130 mg/g), ferulic acid (0.127 mg/g), emodin (0.111 mg/g), and tanshinone IIA (0.005 mg/g).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The major chemical components of SSR, identified by Ultra-High Performance Liquid Chromatography-High Resolution Mass Spectrometry, was reported in our previous study [ 7 ], including rosmarinic acid (21.280 mg/each gram of SSR), amygdalin (6.588 mg/g), salvianolic acid B (1.852 mg/g), caffeic acid (1.390 mg/g), icariin (1.055 mg/g), berberine hydrochloride (0.503 mg/g), codonopsis lactone (0.130 mg/g), ferulic acid (0.127 mg/g), emodin (0.111 mg/g), and tanshinone IIA (0.005 mg/g).…”
Section: Methodsmentioning
confidence: 99%
“…The properties of SSR are including tonifying the spleen and kidney, clearing heat and dampness, and activating blood circulation to resolve stasis. Our previous experimental studies have demonstrated that SSR has potential anti-inflammatory and antifibrotic effects under renal hypoxia condition [ 7–8 ]. Additionally, we found that SSR could improve renal perfusion and reduce renal oxygen consumption in 5/6 renal ablation/infarction (A/I) rats [ 9 ].…”
Section: Introductionmentioning
confidence: 99%